The First Registered Type 0 Spinal Muscular Atrophy Patient in Latvia: Call for Change in Prenatal Diagnostic Procedures - Tīna Luīze Čupāne; Mikus Dīriks; Gita Tauriņa; Liene Korņejeva; Linda Gailīte; Ieva Mālniece; Madara Auzenbaha (Case Reports in Medicine)
This case report presents the first registered patient in Latvia with type 0 spinal muscular atrophy (SMA). During the first-trimester ultrasonography of the unborn patient, an increased thickness of the nuchal fold was detected. The mother reported decreased foetal movements during the pregnancy. After the boy was born, his general condition was extremely severe. The clinical signs indicated a suspected neuromuscular disorder. A precise diagnosis, type 0 SMA, was determined 7 days after birth through a newborn pilot-screening for SMA, which was conducted for all newborns whose parents consented to participate. The condition of the infant deteriorated. He had severe respiratory distress followed by multiple events leading to his death. Currently, there are only a few published case reports detailing an increased nuchal translucency (NT) measurement in association with a diagnosis of SMA in the foetus. However, an increased NT measurement is a clinically relevant sign as it can be related to genetic syndromes, foetal malformations, disruptions, and dysplasias. Since there is no cure for infants with type 0 SMA at present, it is crucial to be able to detect this disease prenatally in order to provide the best possible care for the patient and parents. This includes the provision of palliative care for the patient, among other measures. This case report highlights the prenatal signs and symptoms in relation to type 0 SMA.